Son of the black stallion - Farley, Walter, 1915-1989 (Farley, Walter, 1915-1989. Black stallion series., 2002)
When Alec receives the black stallion's first son as a gift, he believes his dreams have come true, but Satan is a dangerous and unpredictable horse.